STRATEGI GURU BAHASA INDONESIA DALAM MENGATASI KESULITAN MEMBACA KOSAKATA SISWA KELAS II SDN ROUTA KABUPATEN KONAWE - Ummi Kalsum; Subaedah; Muh. Aidil Sudarmono R; Martini; Muhammad Syahrul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the strategies employed by the Indonesian language teacher to address vocabulary reading difficulties among second-grade students at SDN Routa, Konawe Regency, and to identify the factors hindering this process. The study employs a qualitative approach and is classified as field research. The research subjects consist of the Indonesian language teacher and second-grade students. Data collection was conducted through observation, interviews, and documentation, while data analysis involved data reduction, data presentation, and conclusion drawing. The results indicate that the teacher implements two primary strategies: the "word wall" strategy and a motivational strategy. The word wall strategy assists students in recognizing vocabulary, whereas the motivational strategy boosts their self-confidence and interest in reading. Hindering factors include low reading interest, limited instructional media, disparities in student abilities, and a lack of parental support. With appropriate strategies and collaboration among teachers, the school, and parents, students' vocabulary reading difficulties can be overcome.